Stability of Fentanyl Citrate, Hydromorphone Hydrochloride, Ketamine Hydrochloride, Midazolam, Morphine Sulfate, and Pentobarbital Sodium in Polypropylene Syringes - Collin Anderson; Mark MacKay (MDPI AG, 2015)
Purpose: Determine the stability of fentanyl 10 mcg/mL in 0.9% sodium chloride, fentanyl 10 mcg/mL in 5% dextrose, fentanyl 50 mcg/mL, hydromorphone 100 mcg/mL in 0.9% sodium chloride, ketamine 10 mg/mL, midazolam 0.4 mg/mL in 5% dextrose, midazolam 5 mg/mL, morphine 1 mg/mL in 0.9% sodium chloride, morphine 1 mg/mL in 5% dextrose, and pentobarbital 50 mg/mL when stored as single drug entities at room temperature in polypropylene syringes. Methods: Four 5 mL samples of each drug and concentration were prepared in 10 mL polypropylene syringes. The samples were stored at ambient room temperature in a locked cabinet. Triplicate determinations of drug concentration for each sample were performed initially, on day 50 or 51, and on day 100 using high-performance liquid chromatography with diode-array detection. Results: With the exception of the hydromorphone 100 mcg/mL dilution, all compounds were found to contain greater than 95% of their initial concentration remaining at 100 days. Each sample remained clear and colorless when visually inspected.